2009
DOI: 10.26719/2009.15.2.302
|View full text |Cite
|
Sign up to set email alerts
|

Rationale, methods and first results of the Iranian national programme for prevention of chronic diseases from childhood: caspian study

Abstract: The CASPIAN Study aims to implement a school-based surveillance system for prevention of noncommunicable diseases from childhood in the Islamic Republic of Iran. The baseline survey was conducted from November 2003 to May 2004 in 23 provinces among 21 111 school students aged 6-18 years and their parents. The data collected included: birth weight and current anthropometric measurements; dietary and exercise habits; family history of chronic diseases; and knowledge about prevention. Fasting blood sugar and lipi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 30 publications
1
19
0
Order By: Relevance
“…The latest national data in the United States suggest a 17% prevalence of childhood obesity ( 4 ). In Iran according to the childhood and adolescence surveillance and prevention of Iranian adult non-communicable disease (CASPIAN) study, more than 8.8% of school-age children are presently overweight and another 4.5% are obese ( 5 ). Additionally, findings of recent cross-sectional studies conducted in Tehran indicated that overweightness and obesity are highly prevalent among adolescents residing in Tehran ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The latest national data in the United States suggest a 17% prevalence of childhood obesity ( 4 ). In Iran according to the childhood and adolescence surveillance and prevention of Iranian adult non-communicable disease (CASPIAN) study, more than 8.8% of school-age children are presently overweight and another 4.5% are obese ( 5 ). Additionally, findings of recent cross-sectional studies conducted in Tehran indicated that overweightness and obesity are highly prevalent among adolescents residing in Tehran ( 6 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Childhood and Adolescence Surveillance and PreventIon of Adult Noncommunicable Disease (CASPIAN) study, is a national school based surveillance system inspired by World Health Organization (WHO) recommendations, which started on 2003 and has been conducted in four different surveys until 2012. [ 20 ] Detailed methods of the fourth survey are presented elsewhere. [ 21 22 ] In brief, CASPIAN-IV study was a national cross-sectional survey on 14,880 school students, aged 6-18 years.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the total sample size was calculated to be 20, 700 in the 23 provinces, which was increased to 22, 000 to allow for a 5% estimated missing data. The students were selected from elementary, middle and high school by multistage, random cluster sampling from different residence (urban/rural) and different types of schools (public/private) to avoid socioeconomic bias [ 4 , 8 ].…”
Section: Study Population and Sample Sizementioning
confidence: 99%
“…Students knowledge and attitude about CNCD-related risk behaviors questionnaire 5. Parental knowledge and attitude questionnaire Physical measurements Height, weight, waist and hip circumference, blood pressure Height and weight Similar to CASPIAN I study except hip circumference Similar to CASPIAN I study + wrist circumference Lab measurements FBS,TC, HDL-C,TG,LDL-C - Similar to CASPIAN I study+ liver function tests (SGOT,SGPT) - Quality control level -At the district level by local supervisors - Similar to CASPIAN I study - At the district level by academic supervisors -At the national level by a group of statisticians - National supervisors and operator -Evaluation the databank fields for outliers Knowledge dissemination One book [ 4 ] + 20 articles [ 8 - 26 ] One book [ 5 ] One book [ 6 ] + 28 articles [ 27 - 54 ] Book is under preparation + 9 article [ 55 - 63 ] …”
Section: Fundingmentioning
confidence: 99%